Mapping The Colonies: The Directorate of Overseas Surveys' Unexpected Second Chapter - Sheila Masson (Kronos)
Following World War II, the British government created the Directorate of Overseas Surveys (DOS) to aerially photograph, survey and map 55 Commonwealth countries across the globe, including nearly two dozen across Africa. The photographic collection of approximately 1.7 million images is now held by the National Collection of Aerial Photography / Historic Environment Scotland and is part of a modern international digitisation and mapping programme. This article examines the scope of the initial project as well as the unforeseen 21st century benefits and usage, specifically concerning climate change research. Furthermore, it explores contemporaneous colonial attitudes and inherent issues, both then and now, of aerial photography surveillance. Original DOS promotional publications, photographs, maps, annual reports and personnel biographies were examined to gather historic intentions and outcomes. In contrast, modern academic publications help to create a new framework within which to review these historic documents in a postcolonial setting. Key findings reveal the original intent of the project was successful in creating accurate and beneficial mapping of the involved countries, and the preservation and digitisation of the historic photographic archive has produced a 21st century body of data for potential national and global benefit. The DOS archive is a critical document of decades of physical change enacted by the environment, agriculture, commerce and governments. With its roots embedded in wartime aerial reconnaissance, the use of military aircraft blurs the line between surveillance and survey photography. Online access to the digital DOS material will transform its original stated premise of simple territorial mapping into a global archive of scientific data.